Origin of Luminescent Centers and Edge States in Low-Dimensional Lead Halide Perovskites: Controversies, Challenges and Instructive Approaches - Bao, Jiming; Hadjiev, Viktor G. (Nano-Micro Letters, 2019)
With only a few deep-level defect states having a high formation energy and dominance of shallow carrier non-trapping defects, the defect-tolerant electronic and optical properties of lead halide perovskites have made them appealing materials for high-efficiency, low-cost, solar cells and light-emitting devices. As such, recent observations of apparently deep-level and highly luminescent states in low-dimensional perovskites have attracted enormous attention as well as intensive debates. The observed green emission in 2D CsPb2Br5 and 0D Cs4PbBr6 poses an enigma over whether it is originated from intrinsic point defects or simply from highly luminescent CsPbBr3 nanocrystals embedded in the otherwise transparent wide band gap semiconductors. The nature of deep-level edge emission in 2D Ruddlesden–Popper perovskites is also not well understood. In this mini review, the experimental evidences that support the opposing interpretations are analyzed, and challenges and root causes for the controversy are discussed. Shortcomings in the current density functional theory approaches to modeling of properties and intrinsic point defects in lead halide perovskites are also noted. Selected experimental approaches are suggested to better correlate property with structure of a material and help resolve the controversies. Understanding and identification of the origin of luminescent centers will help design and engineer perovskites for wide device applications. Highlights: 1 Controversial luminescent centers and edge states in low-dimensional perovskites were summarized. 2 Evaluated experimental evidences and discussed the root cause for challenges and controversies. 3 New experimental techniques were suggested to resolve the controversies and identify the nature of luminescent centers.